Turkey : Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The assessment is a featured report of Turkey's credit boom in the middle of 2011. The country faced the global crisis successfully because of earlier significant capital buffers. Overall, the country was healthy financially, but there was a slowdown in loan growth and market vulnerabilities. This insignificant shudder caused the regime to strengthen the fiscal sector and insurance framework. Despite new macrofinancial risks in domestic and international developments, the Executive Board still considers Turkey a balanced power.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet